He ion irradiation response of a gradient T91 steel. (1st September 2020) - Shang, Zhongxia; Ding, Jie; Fan, Cuncai; Chen, Di; Li, Jin; Zhang, Yifan; Wang, Yongqiang; Wang, Haiyan; Zhang, Xinghang
Abstract: Metallic materials with a gradient microstructure usually exhibit excellent mechanical properties. However, the radiation response of gradient structural materials is less well understood. Here, room-temperature He ion irradiation up to 4.5 dpa with 10 at% He injection was performed on a gradient T91 steel processed by surface severe plastic deformation. In comparison to the coarse-grained ferritic T91, the gradient T91 with the nanocrystalline layers shows improved radiation tolerance in terms of less bubble swelling and radiation hardening. Additionally, bubble distribution along grain boundaries depends on misorientation angle suggesting a strong capacity of non-equilibrium grain boundaries in storing He atoms. The present study provides insight into the design of radiation tolerant gradient steels for nuclear industry applications. Graphical abstract: Image, graphical abstract